Trial watch: dietary interventions for cancer therapy - Lévesque, Sarah (Oncoimmunology, 2019)
Dietary interventions have a profound impact on whole body metabolism, including oncometabolism (the metabolic features allowing cancer cells to proliferate) and immunometabolism (the catabolic and anabolic reactions that regulate immune responses). Recent preclinical studies demonstrated that multiple dietary changes can improve anticancer immunosurveillance of chemo-, radio- and immunotherapy. These findings have fostered the design of clinical trials evaluating the capacity of dietary interventions to synergize with treatment and hence limit tumor progression. Here, we discuss the scientific rationale for harnessing dietary interventions to improve the efficacy of anticancer therapy and present up-to-date information on clinical trials currently investigating this possibility.